2018
DOI: 10.1016/j.oceaneng.2018.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ship risk model applicability to Marine Autonomous Surface Ships

Abstract: Marine Autonomous Surface Ships (MASS) are tested in public waters. A requirement for MASS to be operated is that they should be at least as safe as conventional ships. Hence, this paper investigates how far the current ship risk models for ship-ship collision, ship-structure collision, and groundings are applicable for risk assessment of MASS. Nine criteria derived from a systems engineering approach are used to assess the relevant ship risk models. These criteria aim at assessing relevant considerations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 71 publications
0
43
0
2
Order By: Relevance
“…Virtually all components of the system will rely on software to the extent that cannot be determined at the point. The fact that some significant uncertainties have been identified pertaining to software solutions feasibility, a further, more comprehensive study on this matter is required (Thieme, Utne, and Haugen 2018). Close cooperation between systems' developers, researchers and practitioners such as seafarers may be extremely beneficial in this matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually all components of the system will rely on software to the extent that cannot be determined at the point. The fact that some significant uncertainties have been identified pertaining to software solutions feasibility, a further, more comprehensive study on this matter is required (Thieme, Utne, and Haugen 2018). Close cooperation between systems' developers, researchers and practitioners such as seafarers may be extremely beneficial in this matter.…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally acknowledged that technical and organizational revolution of shifting merchant vessels' control from their crews to shore-based facilities or on-board computers will influence safety in multiple ways (Nautilus Federation 2018; Ramos et al 2018;Utne, Schjølberg, and Roe 2019;Rødseth and Burmeister 2015). Nevertheless, due to unquestionable innovativeness of the concept and lack of full-scale prototypes operating in a real environment, a comprehensive safety evaluation of the concept could not be performed to date (Thieme, Utne, and Haugen 2018), particularly in a quantitative manner.…”
Section: Introductionmentioning
confidence: 99%
“…The interconnecting variables that link the control problems of different vessels are the predicted trajectories of the ASVs. Thus the information being exchanged, ZX s a consists of the predicted trajectories determined with the control inputs the vessels calculated in each iteration and the nonlinear dynamic model (3).…”
Section: Vessel Train Formationmentioning
confidence: 99%
“…There has been a significant investment by the states and industry to enable autonomous shipping for inland and seagoing vessels. However, there are numerous challenges on the way of having a fully autonomous ship, such as maneuvering control, interaction management with the surrounding environment, efficiency and fault-detection and isolation issues [1], [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Fleming & Leveson (2016) presented a method for analysing future concepts to identify hazardous scenarios at an early stage and allowing safety-driven development of these early concepts. Thieme, Utne, & Haugen (2018) used a systems engineering approach to assess whether current risk models are suitable for application or adaptation to autonomous ships, and found that STPA is a suitable method. Wróbel, Montewka, & Kujala (2018a) identified a control structure for remotely controlled ships and applied STPA based on the control structure.…”
Section: Introductionmentioning
confidence: 99%